PROFESSIONAL IDENTITY OF HIGHER EDUCATION TEACHERS IN SAMPLES OF RIGA AND SMOLENSK - Jermolajeva, Jelena; Bogdanova, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
In most studies on professional identity (PI) of teachers, the subject of research is the PI of a school teacher; far less attention is paid to teachers working at higher education institutions (HEI). The aim of this article is to study the model of HEI teachers’ professional identity by a general comparative analysis of the indicators of its structural components in samples of Riga and Smolensk. The structural components of the proposed model are philosophy of the profession, professional knowledge, professional roles, professional attitude to work, cooperation with colleagues, professional engagement behaviors. To test the relevance of the model, a questionnaire was created with 60 items, and a survey of university teachers was carried out. In total, 198 teachers were surveyed in Riga and Smolensk. The obtained results show the relevance of the proposed model of teachers’ PI and the technique developed to study it. All the components of the model have high average scores and correlate well with each other. The lack of statistically significant differences in both survey samples points out that the PIs of teachers have much in common, regardless of the country of residence and features of the national educational systems. The elaborated technique can be applied as the tool of evaluation/self-evaluation of HEI teachers’ PI to improve the educational process.